The relationship between customer relationship management and customer retention: the mediating effect on customer satisfaction in the telecommunication industry - OKUMO JOSEPHINE KORKOR (KNUST, 2024)
A dissertation submitted to the department of (marketing and strategic management and consulting), school of business in partial fulfilment of the requirement for the degree of master of business administration in strategic management and consulting